CNN-based transfer learning for self-potential inversion - Yian Cui; Xiangbo Yang; Hao Li; Pu Wang; Jing Xie; Jianxin Liu (Earth Science Informatics, 2025)

Probabilistic quantile multiple fourier feature network for lake temperature forecasting: incorporating pinball loss for uncertainty estimation - Siyuan Liu; Jiaxin Deng; Jin Yuan; Weide Li; Xi’an Li; Jing Xu; Shaotong Zhang; Jinran Wu; You-Gan Wang (Earth Science Informatics, 2024)
Lake temperature forecasting is crucial for understanding and mitigating climate change impacts on aquatic ecosystems. The meteorological time series data and their relationship have a high degree of complexity and uncertainty, making it difficult to predict lake temperatures. In this study, we propose a novel approach, Probabilistic Quantile Multiple Fourier Feature Network (QMFFNet), for accurate lake temperature prediction in Qinghai Lake. Utilizing only time series data, our model offers practical and efficient forecasting without the need for additional variables. Our approach integrates quantile loss instead of L2-Norm, enabling probabilistic temperature forecasts as probability distributions. This unique feature quantifies uncertainty, aiding decision-making and risk assessment. Extensive experiments demonstrate the method’s superiority over conventional models, enhancing predictive accuracy and providing reliable uncertainty estimates. This makes our approach a powerful tool for climate research and ecological management in lake temperature forecasting. Innovations in probabilistic forecasting and uncertainty estimation contribute to better climate impact understanding and adaptation in Qinghai Lake and global aquatic systems.

Geological structure identification of coalbed methane reservoir based on trend surface and curvature analysis algorithms - Guoxu Chen; Ruirui Li; Li Cao; Fang Lv; Jing Yuan; Panpan Li; Shengdong Liu; Zhongcheng Li (Earth Science Informatics, 2024)

Wildfire susceptibility prediction using a multisource and spatiotemporal cooperative approach - Jiehang Deng; Weiming Wang; Guosheng Gu; Zhiqiang Chen; Jing Liu; Guobo Xie; Shaowei Weng; Lei Ding; Chuan Li (Earth Science Informatics, 2023)

Influence of adaptive inverse distance weighting method under membership function mapping on the interpolation accuracy of geological boreholes - Huan Liu; Weitao Li; Weibo Zeng; Ling Bao; Yuqing Mei; Jing Guo; Lei Cheng; Shuangxi Gu (Earth Science Informatics, 2023)

Dynamic characteristics of snow frequency and its relationship with climate change on the Tibetan plateau from 2001 to 2015 - Jinbao Liu; Yuting Li; Jing Yu; Yunjun Yao (Earth Science Informatics, 2022)